Wa Lā Taġlū Fī Dīnikum" in Q.S. An-Nisā' (4):171: A Hermeneutic Analysis of Fazlur Rahman's Double Movement in the Context of Religious Moderation in the Post-Truth Era - Akhmad Aidil Fitra; Asnaini; Nuri Nurhaidah, Siti; Sirajuddin, Sirajuddin; Rizkita, Muhammad (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
The phenomenon of rising religious populism, digital radicalism, and theological disinformation in the post-truth era has shifted religious authority from clerics and academics to a digital space full of emotions and ideological biases. This condition gave rise to a new form of ghuluw (extremism) that was not only theological, but also epistemological. This research aims to answer the main question: what is the meaning of "wa lā taghlū fī dīnikum" in Q.S. An-Nisā' (4):171 can be interpreted through Fazlur Rahman's double movement hermeneutics to strengthen the paradigm of religious moderation in the post-truth era? Using a qualitative approach based on literature studies, this study utilizes Fazlur Rahman's major work Themes of the Qur'an and Islam and Modernity as a theoretical foundation, and is supported by classical and contemporary interpretations for textual analysis. The data analysis technique is carried out through two stages of double movement: understanding the historical context of the revelation (the first movement) and relevanting it to modern socio-religious conditions (the second movement). The results of the study show that the prohibition of ghuluw in the verse has universal moral relevance as a warning against the absolutism of interpretation and the claim of the single truth in the age of disinformation. Through the double movement approach, it is found that religious moderation is not an ideological compromise, but a rational expression of Qur'anic ethics that integrates faith, reason, and humanity. This research offers an epistemological synthesis in the form of "contextual-moderate interpretation", which is an integrative interpretive model between texts, contexts, and social morals. This study recommends the development of further research on the integration of Rahman's hermeneutics with maqāṣid al-sharī'ah and religious digital literacy theory to strengthen the epistemic resilience of the ummah in the midst of a global crisis of truth